2010
DOI: 10.1007/s00125-010-1663-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of liver fat vs visceral fat in determining categories of prediabetes

Abstract: Aims/hypothesis Impaired fasting glucose (IFG) and impaired glucose tolerance (IGT) are risk factors for type 2 diabetes and cardiovascular disease; however, their impact on these endpoints differs. Because liver fat and visceral fat are important determinants of glucose and lipid metabolism, we investigated whether these fat compartments and their humoral products, the adipokine adiponectin and the hepatokine fetuin-A, differ in their impact on the glucose categories. Methods In 330 individuals at risk of typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 52 publications
11
94
2
4
Order By: Relevance
“…When estimated by the HOMA-IR, insulin resistance at follow-up was close to the cut-off of 2.5 that is associated with clamp-measured insulin resistance [5], indicating that OIR individuals remained essentially insulin resistant despite the intervention. The same trend was noted with regards to body fat distribution and ectopic fat deposition, which is a major determinant of the MHO vs the OIR status [6] and of prediabetes [17]. Certainly, it may well be that a longer duration of our relatively intense intervention may have yielded more positive results for the OIR individuals.…”
Section: Discussionsupporting
confidence: 62%
“…When estimated by the HOMA-IR, insulin resistance at follow-up was close to the cut-off of 2.5 that is associated with clamp-measured insulin resistance [5], indicating that OIR individuals remained essentially insulin resistant despite the intervention. The same trend was noted with regards to body fat distribution and ectopic fat deposition, which is a major determinant of the MHO vs the OIR status [6] and of prediabetes [17]. Certainly, it may well be that a longer duration of our relatively intense intervention may have yielded more positive results for the OIR individuals.…”
Section: Discussionsupporting
confidence: 62%
“…Elevated plasma Fetuin-A levels positively predict the incidence of T2DM independent of other established risk factors (Ix et al, 2008;Stefan et al, 2008). In a study of 330 adults at risk for T2DM, liver fat was the strongest predictor of prediabetes (Kantartzis et al, 2010) (Kantartzis et al, 2010). Among studied biochemical measures, serum Fetuin-A was a more significant predictor of fasting hyperglycemia than serum adiponectin (Kantartzis et al, 2010).…”
Section: Metabolic Syndrome and Emerging Non-traditional Risk Factorsmentioning
confidence: 96%
“…In a study of 330 adults at risk for T2DM, liver fat was the strongest predictor of prediabetes (Kantartzis et al, 2010) (Kantartzis et al, 2010). Among studied biochemical measures, serum Fetuin-A was a more significant predictor of fasting hyperglycemia than serum adiponectin (Kantartzis et al, 2010). In addition, individual liver enzymes, such as alanine aminotransferase, have varying positive associations with the components of the metabolic syndrome (Zhang et al, 2010).…”
Section: Metabolic Syndrome and Emerging Non-traditional Risk Factorsmentioning
confidence: 99%
“…Several studies have demonstrated that the quantity of liver fat is more closely linked to the metabolic complications of obesity than that of visceral fat [7][8][9] . However, there is conflicting evidence that suggests excess visceral fat and insulin resistance, but not general adiposity are associated with incident pre-diabetes and type 2 diabetes in obese individuals 10 .…”
Section: Introductionmentioning
confidence: 99%